2013
DOI: 10.1103/physrevlett.111.061102
|View full text |Cite
|
Sign up to set email alerts
|

First Results from the CARIBU Facility: Mass Measurements on ther-Process Path

Abstract: The Canadian Penning Trap mass spectrometer has made mass measurements of 33 neutron-rich nuclides provided by the new Californium Rare Isotope Breeder Upgrade facility at Argonne National Laboratory. The studied region includes the 132Sn double shell closure and ranges in Z from In to Cs, with Sn isotopes measured out to A=135, and the typical measurement precision is at the 100 ppb level or better. The region encompasses a possible major waiting point of the astrophysical r process, and the impact of the mas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 46 publications
3
56
0
Order By: Relevance
“…A large effort has been devoted to the measurement of masses, β -decay half-lives, and β -delayed neutron emission probabilities (e.g. recently [3][4][5]), however, the majority of the r-process nuclei are still not accessible. In addition, although in many environments the neutron-capture reaction rates do not play significant role in the r-process flow due to (n, γ)-(γ, n) equilib- * spyrou@nscl.msu.edu † liddick@nscl.msu.edu ‡ a.c.larsen@fys.uio.no rium, recent studies have shown significant sensitivity to the neutron-capture reaction rates in certain conditions [6].…”
mentioning
confidence: 99%
“…A large effort has been devoted to the measurement of masses, β -decay half-lives, and β -delayed neutron emission probabilities (e.g. recently [3][4][5]), however, the majority of the r-process nuclei are still not accessible. In addition, although in many environments the neutron-capture reaction rates do not play significant role in the r-process flow due to (n, γ)-(γ, n) equilib- * spyrou@nscl.msu.edu † liddick@nscl.msu.edu ‡ a.c.larsen@fys.uio.no rium, recent studies have shown significant sensitivity to the neutron-capture reaction rates in certain conditions [6].…”
mentioning
confidence: 99%
“…Daniel Lascar played a significant role in getting the CPT moved to CARIBU and then used the facility to measure the masses of some 24 nuclei in the r-process path. These measurements, along with other mass measurements done at CARIBU, have shown that previous determinations from beta-decay data and from models are inaccurate by as much as hundreds of keV [9]. Dr. Lascar completed his PhD in 2012 and is now working in industry.…”
Section: Nuclear Mass Measurementsmentioning
confidence: 95%
“…The highlights after AME2012 are mass measurements of very neutron rich nuclides by the ISOLTRAP group [9,16] and the first results from the CARIBU facility [17]. At the RI Beam Factory at RIKEN, many new nuclides very rich in neutron were discovered.…”
Section: Mass Measurements After Ame2012mentioning
confidence: 99%